Transient overexpression of Pparγ2 and C/ebpα in mesenchymal stem cells induces brown adipose tissue formation. (May 2013) - Sheyn, Dmitriy; Pelled, Gadi; Tawackoli, Wafa; Su, Susan; Ben-David, Shiran; Gazit, Dan; Gazit, Zulma
Background: Brown adipose tissue plays a pivotal role in mammal metabolism and thermogenesis. It has a great therapeutic potential in several metabolic disorders such as obesity and diabetes. Mesenchymal stem cells (MSCs) are suitable candidates for brown adipose tissue formation de novo . Pparγ2 and C/ebpα are nucleic receptors known to mediate adipogenic differentiation. We hypothesized that overexpression of the Ppar γ 2 and C/ebp α genes in MSCs would lead to the formation of adipose tissue.Materials & methods: MSCs bearing the Luc reporter gene were transfected to overexpress Ppar γ 2 and C/ebp α. Differentiation of nucleofected cells was evaluated in vitro and in vivo following ectopic implantation of the cells in C3H/HeN mice.Results: After implantation, the engineered cells survived for 5 weeks and brown adipose-like tissue was observed in histological samples. Immunostaining and bioluminescent imaging showed new adipocytes expressing Luc and the brown adipose tissue marker, UCP1, in vitro and in vivo .Conclusion: We show that gene delivery of transcription factors into MSCs generates brown adipose tissue in vitro and in vivo .